Sosialisasi Pembentukan Kerja Sama Antar Daerah untuk Aparat Pemerintah Kabupaten Tanjung Jabung Barat - Hardiani; Junaidi; Purwaka; Etik Umiyati; Adi Bhakti (WIDA Publishing, 2022)
The community engagement activity aims to: 1) Provide understanding to officials and policy makers in the West Tanjung Jabung Regency Government about the role and importance of interregional cooperation in accelerating development; 2) Enhance the practical knowledge of officials and policy makers in the West Tanjung Jabung Regency Government in designing the establishment of interregional cooperation institutions. The methods employed in this socialization activity include lectures, discussions, audiovisual presentations, and evaluations. During the lectures, knowledge materials cover the philosophy, basic concepts, and understanding of interregional cooperation; general principles of interregional cooperation; various forms of interregional cooperation; legal foundations of interregional cooperation; interregional cooperation experiences in Europe and Asia; and technical aspects of implementing interregional cooperation in Indonesia. Through discussions, participants are trained to articulate ideas and key points related to interregional cooperation. Additionally, audiovisual tools are utilized to present materials, case studies, and challenges related to interregional cooperation as a means to enhance participants' interest and motivation in the socialization process. The results of this community engagement activity conducted by the University of Jambi's community engagement team received positive responses from the participants. This is evident from the high level of participation in discussions and the emergence of statements from participants highlighting the importance of establishing interregional cooperation between West Tanjung Jabung Regency and other regencies to enhance the development of West Tanjung Jabung Regency.